Formação e dissolução de uma comunidade religiosa : um estudo das Testemunhas de Jeová em Mairipotaba, Goiás (1992-2007) - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Few are the works that account for Jehovah's Witnesses in Brazil, especially in the context of the history of religions. Knowing this, we strive to focus on a particular historical reality in the interior of Goiás, which, in the context of the history of religions, implies attention to a specific religious plot that cannot be reduced exclusively to generalizing readings. The religious group in question was born in the United States, became global and effectively entered Brazil in 1922. There is, in this sense, a dialectic between the global and the local that runs through the religious life of Jehovah's Witnesses and is related to destiny of the group in Mairipotaba. Therefore, this research was divided into three parts: in the first chapter we deal directly with the emergence of the group of Bible Students that gave rise to the Jehovah's Witnesses, the second chapter with the historical dimension of the expansion of the religious group to other countries, in particular, their arrival in Brazil, as well as their installation in Goiás, and, finally, the group's arrival in the interior of Goiás and the relationships established between the Witnesses and the community based on the relationships described there.
Keywords: Religiões; Instituição religiosa; Testemunhas de Jeová; Religions; Religious institution; Jehovah's Witnesses; HISTORIA DO BRASIL::HISTORIA REGIONAL DO BRASIL